Helping International Students Identify Themselves: Social Media Usage and Organizational Attachment - Valdez Paez, Gustavo; Hou, Ning; Tan, James; Wang, Zhan; Hua, Jing (Journal of International Students, 2021)
The relationship between social media usage and personality has received increased scrutiny recently. The current study studies international students’ organizational attachment through the exploration of their personality and usage of university social media. Participants were 51 international students from a Midwest State University and 49 domestic (U.S.) students for comparison purposes. Results showed some differences in the structure of personality, level of social media usage, and level of organizational attachment comparing international students and domestic students. Results also supported the complementary purpose of using social media for international students, where agreeableness and openness to experience are negatively associated with social media usage. Moreover, the relationship was stronger when students’ English proficiency is lower. An overall model demonstrated the relationship among international students’ personalities, university social media usage, and organizational attachment.